Development of case tool to convert class diagram to physical database / Rosli Ismail - Ismail, Rosli (2006)
The purpose of this study is to review on the methodology used in software development where the researcher will focus more on the Class diagram and Physical Database. From this review the researcher will find out the requirement of transformation to transform the Class Diagram into Physical Database and these requirements will be applied in developing the CASE tool that can transform the Glass Diagram into Physical Database, the researcher also will state significant analysis and findings of the CASE tool which has been developed.